Supplementing glycine, serine, and threonine in low protein diets for meat type chickens. (21st August 2019) - Hilliar, M; Huyen, N; Girish, C K; Barekatain, R; Wu, S; Swick, R A
ABSTRACT: Reducing dietary protein has been of interest to the global poultry industry to improve bird health, welfare, and industry sustainability. Low protein (LP ) diets are typically glycine (Gly ) deficient and produce poor performance. Supplementing the diet with Gly or precursors of Gly can overcome this deficiency. A feeding experiment was conducted with 330 Ross 308 off-sex males across 5 treatments in a randomized design using 11 birds per pen replicated 6 times. Grower and finisher treatments were fed from day 7 to 21 and day 21 to 35, respectively. The objective was to test the efficacy of supplementation with Gly and Gly equivalents (Glyequiv ), serine (Ser ) and threonine (Thr ), in plant-based LP diets on bird performance against a standard protein (SP ) diet containing meat and bone meal. Glycine, Ser, or Thr were supplemented on Glyequiv basis to an approximately 3% lower CP diet to achieve the same digestible Gly and Ser level as the SP diet. Nitrogen efficiency, serum uric acid, blood plasma amino acids (AA) and AA digestibility were also investigated to monitor potential metabolic effects. Birds fed the LP diet were only 3.3% lower in final body weight than the SP treatment (2, 556 vs. 2, 641 g) while the supplementation of Gly or Ser had no effect. Supplementation of Thr reduced final body weight by 9.5% ( P < 0.05). Reducing CP increased N efficiency by 9.6% ( P < 0.05) and decreased blood serum uric acid by 26.9% ( P < 0.001) in the finisher treatments. Glycine and Ser supplementation in LP diets had no effect on these parameters. The LP diet reduced AA digestibility and blood plasma AA while the supplementation with either Gly, Ser, or Thr increased overall AA digestibility ( P < 0.05) but had no overall effect on blood plasma AA. Further research is required into Gly metabolism; however, Thr supplementation depressed growth and therefore is not feasible to cover Gly deficiency in LP diets on a Glyequiv basis.